THE GENEALOGY OF MARRIAGE HADITH INTERPRETATION: Power, Knowledge, and Islamic Family Law in Fath al-Mun'im Sharh Sahih Muslim - Yunus, Adynata bin; Chandra, Agus Firdaus; Ikromi, Zul; Hayati, Safira Malia; Marsal, Arif (RIWAYAH, 2026)
Interpretations of hadiths on marriage have commonly been treated as objective and normative religious explanations, despite being shaped by historical, intellectual, and sociopolitical contexts. While previous studies have primarily examined marriage hadiths through legal, theological, or textual approaches, limited attention has been given to the power relations underlying their interpretation. This study investigates the genealogy of marriage hadith interpretation in Fath al-Mun’im Sharh Sahih Muslim by Musa Syahin Lasyin through Michel Foucault’s genealogical framework. Employing qualitative library research, the study analyzes Fath al-Mun’im  as its primary source to trace the formation of interpretive discourse, the operation of power relations, and the production of knowledge embedded in the commentary. The findings reveal that Lasyin’s interpretation is not derived solely from the authority of hadith texts or the classical commentary tradition but is constructed through the interaction of fiqh heritage, Al-Azhar’s institutional authority, and the sociopolitical realities of modern Egypt. This interaction produces an epistemological shift from a predominantly normative legal orientation toward a maqasid-based and socio-contextual reading, particularly in discussions of marriage, betrothal, spousal relations, and women’s rights. The study concludes that hadith interpretation constitutes a dynamic discursive practice in which textual authority, institutional knowledge, and power relations continuously shape religious meaning. By integrating Foucauldian genealogy into hadith studies, this research contributes a critical analytical framework for understanding hadith commentaries as historically contingent sites of knowledge production rather than merely neutral textual expositions.Penafsiran hadis-hadis tentang pernikahan selama ini umumnya dipahami sebagai penjelasan keagamaan yang bersifat objektif dan normatif, meskipun sesungguhnya dibentuk oleh konteks historis, intelektual, dan sosial-politik. Sementara penelitian terdahulu lebih banyak mengkaji hadis pernikahan melalui pendekatan hukum, teologi, atau analisis tekstual, perhatian terhadap relasi kuasa yang melatarbelakangi proses penafsirannya masih terbatas. Penelitian ini bertujuan menganalisis genealogi penafsiran hadis-hadis pernikahan dalam Fath al-Mun’im Syarh Sahih Muslim karya Musa Syahin Lasyin dengan menggunakan kerangka genealogi Michel Foucault. Penelitian ini merupakan penelitian kualitatif berbasis kepustakaan dengan menjadikan Fath al-Mun’im sebagai sumber data utama untuk menelusuri pembentukan diskursus penafsiran, relasi kuasa, dan produksi pengetahuan yang terkandung dalam kitab tersebut. Hasil penelitian menunjukkan bahwa penafsiran Lasyin tidak semata-mata bertumpu pada otoritas teks hadis maupun tradisi syarah klasik, tetapi dikonstruksi melalui interaksi antara warisan fikih, otoritas kelembagaan Al-Azhar, dan dinamika sosial-politik Mesir modern. Interaksi tersebut menghasilkan pergeseran epistemologis dari orientasi hukum yang normatif menuju pembacaan yang berorientasi pada maqasid dan kontekstual, khususnya dalam pembahasan mengenai pernikahan, peminangan, relasi suami-istri, dan hak-hak perempuan. Penelitian ini menyimpulkan bahwa penafsiran hadis merupakan praktik diskursif yang dinamis, di mana otoritas teks, produksi pengetahuan, dan relasi kuasa secara terus-menerus membentuk makna keagamaan. Dengan mengintegrasikan pendekatan genealogi Foucauldian ke dalam studi hadis, penelitian ini memberikan kontribusi berupa kerangka analisis kritis untuk memahami kitab-kitab syarah hadis sebagai ruang produksi pengetahuan yang bersifat historis dan dinamis, bukan sekadar penjelasan tekstual yang netral.